Biorremediação de efluente contaminado com cromo utilizando Spirulina platensis - Lopes, Erisson Paulo Borges (2023)
Bioaccumulation and biosorption in cyanobacteria are effective approaches for the removal of heavy metals (HMs) from wastewater. The objective of this work was to investigate the potential use of the cyanobacterium Spirulina platensis in the phycoremediation of hexavalent chromium - Cr (VI) and total chromium, as well as to evaluate the effect of this contamination on the production of biomass and photosynthesizing pigments. For this, a growth kinetics assay of the active culture was performed with the intention of choosing the inoculum at the maximum concentration for the phycoremediation assays. The inoculum was then prepared at a concentration of 1.2 ± 0,02 g/L in a static reactor, 500 mL erlenmeyer flask, containing hexavalent chromium fed at concentrations of 10, 30, and 60 mg/L, under an average ambient temperature of 28°C ± 1°C under a 12-hour photoperiod at 3500 lux and 10-day fermentation. The presence of hexavalent chromium caused the inhibition of growth and photosynthesis of pigment production. After 10 days of the fermentation process, all hexavalent chromium was biosorbed and bioaccumulated by S. platensis, which also showed high average total chromium removal efficiency 76%, 86% and 88% for the trials with Cr (VI) feed at 10, 30 and 60 mg/L, respectively. The tubular photobioreactor promoted the development of significantly greater biomass than static bioremediation; however, the effect on chromium removal was not observed. The findings demonstrated that S. platensis is a cyanobacterium with the potential for Cr (VI) sequestration, with exceptions to its cell growth, which was circumvented using a photobioreactor.